Association between leptin gene polymorphism and growth traits in Bali cattle - T. Kurlyana; T. Hartatik; S. Sumadi (Diponegoro University, 2023)
Leptin (LEP) gene produces hormone leptin which is secreted by adipose tissue, and plays an im-portant role in energy balance, regulating feed intake, regulating endocrine function, and immune functions. This study aims to identify molecular markers of LEP gene and its association with growth traits based on SNP in Bali cattle. The blood samples were collected from 16 male and 30 female Bali cattle. The growth data were recorded from 2018 to 2020, consist of body weight and body size. Am-plification of leptin gene with polymerase chain reaction (PCR) using pair of primers, Lep-tin_3Forward: 5’- AGCTTGGAAACATGGTGGTC-3’ and Leptin_3Reverse: 5’- CATGATGCTCCCTGGATTCT-3’ with DNA target 898 bp. The SNPs were identified by the direct sequencing technique. Genotypes of the SNPs were identified using sequencing method. Association of LEP genotypes with growth traits was performed using oneway ANOVA. Three DNA polymor-phisms of the LEP gene were found, namely g.2913C/T, g.3260T/C, and g.3549G/A. SNP g.2913C/T was significantly associated (P<0,05) with weaning shoulder height (WSH), weaning body length (WBL), weaning chest circumference (WCC), yearling shoulder height (YSH), yearling body length (YBL), and yearling chest circumference (YCC). Meanwhile, SNPs g.3260T/C and g.3549G/A were not associated with the body weight and body size in Bali cattle. In conclusion, the SNP g.2913C/T can be used as molecular marker for body size in weaning and yearling of Bali Cattle.